Amniotic Fluid and Placental Membranes: Unexpected Sources of Highly Multipotent Cells - Murphy, Sean V.; Atala, Anthony (Seminars in Reproductive Medicine, 2013)
Gestational tissue such as the placenta, placental membranes, and amniotic fluid are usually discarded following birth. Recently, researchers have identified gestational tissue as an untapped source of stem cells that are highly multipotent and possess potent immunosuppressive properties. Placental mesenchymal stem cells (MSCs), human amnion epithelial cells (hAECs), and amniotic fluid–derived stem cells (AFSCs) have been shown to differentiate into various cell types including adipogenic, osteogenic, myogenic, endothelial, pulmonary, neurogenic, hepatogenic, cardiac, and pancreatic lineages. Their immunomodulatory properties suggest that gestational stem cells may have an important application in the treatment of various inflammatory diseases such as graft versus host and autoimmune diseases. In clinical and preclinical studies, gestational stem cells have shown efficacy in the treatment of Crohn disease, lung disease, diabetes, repair of bone defects, heart disease, kidney disease, neural degeneration, and blood disorders. Stem cells derived from the placenta, placental membranes, and amniotic fluid are a valuable resource for the field of regenerative medicine.
Keywords: placenta; amniotic; fluid; membrane; stem cells